WACANA PEREMPUAN DAN POLITIK DI MEDIA MASSA (ANALISIS WACANA PEMBERITAAN PEREMPUAN DALAM KONSTELASI PEMILIHAN PRESIDEN TAHUN 2019 PADA MEDIA ONLINE KOMPAS.COM) (Fakultas Dakwah dan Komunikasi, 2021)
The objectives of this study are: 1) to find out the structure of women's news stories in the 2019 presidential election constellation at Kompas.com which includes macro, superstructure, and microstructures, and 2) women's discourse in the 2019 presidential election constellation on Kompas.com Media. . The results of this study indicate that the topic or theme raised has not yet raised women as parties who have power like men in politics. In addition, there are many popular themes that place women as figures who seem only interested in good looks or men's physique. The superstructure or framework of a text also still shows emphasis and prioritizes statements that show the power of men over women. Meanwhile, the microstructure found that there are various languages used to refer to women, namely mothers, mothers, and mothers, each of which contains a bias towards social class and seems to limit the role of women. Women in the constellation of the 2019 presidential election are still being discoursed as a male-dominated party. Politics is still identified with aggressiveness which is generally attached to the masculine image. So that women's support groups are still vulnerable to bad stereotypes in society.